Mask mandates, race, and protests of summer 2020. Issue 3 (3rd September 2022) - Rahman, Rahbel; Azhar, Sameena; Wernick, Laura J.; DeVylder, Jordan E.; Maschi, Tina; Cohen, Margaret; Hopwood, Simone
ABSTRACT: This study examined predictors to mask mandate support and racial justice protest participation across Asian (n = 103), Black (n = 102), white (n = 102) New York City residents, using binary logistic regressions. Participants with positive feelings about the racial justice movement were more likely to participate in the protests. White and Asian respondents were more likely to support the mask mandates over Black respondents. Asian respondents were less likely to participate in public protests over white respondents. Our findings offer a model for social workers to understand how race, political participation and COVID-19 intersect to create racially just responses to health and justice matters.